RANCANG BANGUN WEBSITE E-COMMERCE ANEKA TAS DAN KERAJINAN BAMBU TOKO RAJAPOLAH (Information Technology and Telematics, 2015)
Abstract : E-commerce is where in one website providing or may conduct transactions online or also can be a way to shop or trade online or direct selling are utilizing the Internet facility where there are websites that can provide services "get and deliver". E-commerce will change all marketing activities and also while cutting operational costs for trading activities (trading). Ecommerce for electronic commerce (English: electronic commerce or e-commerce) is the deployment, purchasing, sales, marketing goods and services over electronic systems such as the Internet expands the range of promotional and selling online as the trade through electronic media connected to the Internet. The process, as well as delivery or perantra aagen. With the system of E-commerce or online allows customers do tranaksi reservation for 24 hours and provide more choices analysis of sales systems that exist today., It is known that the system is needed is a system that can make sales online, manage product data, order products, checks inventory and customer data ever transaction. And result system is designed and built using PHP, Apache as the web server, and as a framework bootstrap web interface. Keywords: ecommerce, bootstrap Abstrak